3D stereophotogrammetry: post-processing and surface integration. (February 2015) - Catherwood, T. E.; Winder, J. A.; McIntosh, S. A.; Winder, R. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Three-dimensional surface imaging has the potential to add value to the visualisation of external and internal human anatomy. Stereophotogrammetry surfaces were acquired from multiple viewpoints and integrated to form a digital model. Artefacts due to line-of-sight, surface colour and reflectance were found to result in holes and geometric distortion. Surface artefacts were corrected using CAD techniques and validated. Errors between 0·2 and 2·0 mm occurred in repaired surfaces, while geometric distortion ranged from 1·9 to 7·4 mm during surface registration. Post-processing and surface integration techniques may expand the capability of multi-headed stereophotogrammetry systems to assess a wide range of medical conditions.